(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This article brings an analysis of the scene costume in the film universe, from the movie Marighella, which has the costume composition developed by costume designer Veronica Julian, who brings a thorough and dedicated work in the production with an entire team. With a narrative inspired by the biography of the Bahian guerilla Carlos Marighella, the feature film, directed by Wagner Moura, chooses to portray the last five years of life of the founder of the Ação Libertadora Nacional. The study of the costumes is based primarily on the work of film and costume theorists, and on an interview conducted with the costume designer by the author. From the references and the material analyzed it was possible to better understand the choice of wardrobe of the characters, as well as the use of colors and material applied to each of them and realize the importance of integration and harmony between costumes, scenery and artistic production as a whole for the visual composition of a movie.